The Ukraine war and its food security implications for India - S. J., Balaji; Babu, Suresh Chandra (International Food Policy Research Institute, 2022)
Russia’s war on Ukraine shows no signs of subsidence. Its economic and societal adversities have already been felt worldwide but keep evolving, with food and energy being the most affected. Low-income, food-deficit nations importing from these two countries – many of which are in Northern Africa and Western and Central Asia – face critical challenges. The South Asian region, which has grappled with surging commodity prices and supply constraints even before the war, is likely to witness further inflation with rising food and oil prices. India is home to around 18% of the world’s population and accounts for 74% of the South Asian population. It is predicted to be the fastest-growing big economy this year. The country’s central bank (RBI) predicts that GDP will grow by 7.5% in FY 2022-23 (RBI, 2022), while many international organizations forecast growth between 6.4% and 8.2% (ADB, 2022; IMF, 2022; United Nations, 2022; World Bank, 2022). Still, in the wake of the ill effects of COVID-19, the country’s dependence on imports such as oil, fertilizers, and edible oils, and given surging domestic food and nonfood inflation in recent months, raises concerns about economic stability and possible interventions that might curtail fragility. The country consumes around 5 million barrels of crude oil daily but imports over 89% of its requirement from overseas. Crude oil prices have increased by 27% in just four months since the start of the war (February- June 2022). Edible oils have similarly increased, with palm and soybean oil prices rising by around 14% and 18%, respectively. The price of sunflower seed oil has increased by 42%, of which 86% originates from Ukraine and Russia. Fertilizer import dependency from the conflict regions is also sizeable. Russia was the 5th largest supplier of fertilizers to India in 2021-22, and Ukraine and Belarus were the 9th and 10th largest suppliers. The rise in prices of both finished fertilizers and fertilizer inputs has prompted the Government to double the fertilizer subsidy budgeted earlier this year. This policy brief investigates India's susceptibility to the war's disruptions and higher prices for commodities where import dependence is high. It then discusses potential income, food, and nutritional impacts on farmers, the poor, and the vulnerable. It also evaluates the Government’s policy measures such as subsidization, social safety nets, and trade diversification to reduce the impact of the war. Finally, it explores the market opportunities the conflict has created and the required structural reforms that would equip the country to handle such shocks in the future